A General Convergent Strategy for the Synthesis of Tetra‐Substituted Furan Fatty Acids (FuFAs). Issue 19 (20th March 2020) - Wang, Yamin; Pritchard, Gareth J.; Kimber, Marc C.
Abstract : Using a palladium catalyzed ‐ acid mediated isomerization sequence, tetrasubstituted furans suitable for furan fatty acid (FuFA) total synthesis can be effectively constructed in high yield. This convergent approach installs the essential carbon side chains at the α1 ‐ and α2 ‐positions, the β1 ‐methyl group, and importantly, an electron withdrawing group at the β2 ‐position tempering the reactivity of the electron rich furan in the FuFAs. When this EWG is an ester, it was conveniently transformed into the required β1 ‐methyl group in three high yielding synthetic steps. Using this approach, the total synthesis of 11D5 and 11D3 was accomplished in 7‐steps from commercially available starting materials in overall yields of 52 % and 48 %, respectively. Furthermore, this methodology also provided an efficient synthetic route to the decarboxy analogues of both 11D5 and 11D3. Abstract : Tetrasubstituted Furan Fatty acids (FuFAs) are a vital and ubiquitous class of natural products, that upon ingestion afford significant health benefits. Herein, a general and modular approach to their total synthesis is presented, delivering short yet efficient syntheses of two key FuFAs, 11D3 (F4 ) and 11D5 (F6 ), in 52 % and 48 % overall yield, respectively. Significantly, this method offers an effective route to key analogues, such as decarboxy‐11D3 and decarboxy‐11D5.